CARM1 Regulates Estrogen-Stimulated Breast Cancer Growth through Up-regulation of E2F1 - Frietze, Seth; Lupien, Mathieu; Silver, Pamela A.; Brown, Myles (Cancer research (Chicago, Ill.), 2008)
Estrogen receptor α (ERα) mediates breast cancer proliferation through transcriptional mechanisms involving the recruitment of specific coregulator complexes to the promoters of cell cycle genes. The coactivator-associated arginine methyltransferase CARM1 is a positive regulator of ERα-mediated transcriptional activation. Here, we show that CARM1 is essential for estrogen-induced cell cycle progression in the MCF-7 breast cancer cell line. CARM1 is specifically required for the estrogen-induced expression of the critical cell cycle transcriptional regulator E2F1 whereas estrogen stimulation of cyclin D1 is CARM1 independent. Upon estrogen stimulation, the E2F1 promoter is subject to CARM1-dependent dimethylation on histone H3 arginine 17 (H3R17me2) in a process that parallels the recruitment of ERα. Additionally, we find that the recruitment of CARM1 and subsequent histone arginine dimethylation are dependent on the presence of the oncogenic coactivator AIB1. Thus, CARM1 is a critical factor in the pathway of estrogen-stimulated breast cancer growth downstream of ERα and AIB1 and upstream of the cell cycle regulatory transcription factor E2F1. These studies identify CARM1 as a potential new target in the treatment of estrogen-dependent breast cancer. [Cancer Res 2008;68(1):301–6]